The Case/Care Manager in Eating Disorders: the nurse’s role and responsibilities: Case/Care Manager in Eating Disorders - Foà, Chiara; Bertuol, Maria; Deiana, Laura; Rossi, Sandra; Sarli, Leopoldo; Artioli , Giovanna (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Despite its incidence, the Eating Disorder (ED) is underdiagnosed and, for its complexity, it requires multidisciplinary interventions. The Nurse and Case/Care Manager (CCM) have a central role in taking care of the patients with ED, even if the research concerning their role are lacking. Thus, the aim of the study was to investigate roles, activities and expectations of the nurse and the CCM in taking care of patients with ED. Method: 25 Italian different professionals were interviewed (16 women, average age 43.4; SD = 9.23). The semi-structured interview has investigated: nurses’ roles and activities; perceptions of nurses’ evaluation; expectations on nurses’ and CCM’s roles; the interprofessional collaboration. Results: The nurses analyse patients’ care needs and coordinate the multi-professional care with empathic attitude. Their “professionalism, skills, sensitivity, ability to relate to the patient-family unit” are expectations shared by various professionals. About the interprofessional collaboration, the action of professionals is not always well coordinated, the decisions are often not shared and hospital-territory connection is not always realised. The CCM would be the reference in this process for all interviewees. Conclusions: In the three examined contexts the figure of the CCM was not present, but his/her importance was acknowledged in the management of the patient’s care path and as a point of reference for health professionals. It seems important that CCM is institutionally recognized, because the CCM would ensure an efficient management of the clinical pathway and would guarantee the continuity and appropriateness of care.